2017
DOI: 10.1111/1751-2980.12498
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 10‐day levofloxacin bismuth‐based quadruple therapy and levofloxacin‐based triple therapy for Helicobacter pylori

Abstract: Adding bismuth subcitrate to levofloxacin-based triple therapy was not more effective than not doing so, but no further side effects were noted. Both eradication therapies were equally safe and patients had the same tolerance to both regimens. Resistance rate to levofloxacin may be important when choosing second-line therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…To increase the success rates of quinolone triple therapies, some (379)(380)(381) . studies have added bismuth salt to the regimen, which provided good results for eradication (398,399) . Quadruple bismuth therapy (PPI, bismuth, tetracycline, and metronidazole) is usually recommended during retreatment, with eradication rates approaching 80% (392) .…”
Section: Level Of Evidence: 2a Grade Of Recommendation: Bmentioning
confidence: 99%
“…To increase the success rates of quinolone triple therapies, some (379)(380)(381) . studies have added bismuth salt to the regimen, which provided good results for eradication (398,399) . Quadruple bismuth therapy (PPI, bismuth, tetracycline, and metronidazole) is usually recommended during retreatment, with eradication rates approaching 80% (392) .…”
Section: Level Of Evidence: 2a Grade Of Recommendation: Bmentioning
confidence: 99%
“…In another study, the e cacy of adding bismuth to a levo oxacin-based triple regimen (rabeprazole, bismuth, amoxicillin, and 500 mg of levo oxacin daily) assessed. The results revealed no further signi cant eradication rat (67.6%), but no more ADRs were noted [40].…”
Section: Discussionmentioning
confidence: 82%
“…A further study from Taiwan demonstrated higher eradication rates with levofloxacin‐based concomitant therapy (96.4%) compared to sequential therapy (81.4%) . The addition of bismuth to levofloxacin‐based triple therapy, however, in areas with low levofloxacin resistance does not confer any further benefit …”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…34 The addition of bismuth to levofloxacin-based triple therapy, however, in areas with low levofloxacin resistance does not confer any further benefit. 35 A retrospective study assessing the utility of a moxifloxacinbased triple therapy reported eradication rates of 80% following hybrid therapy failure. 36 Quinolone-based rescue therapies are more successful in bismuth-containing quadruple therapies, with longer duration (10-14 days) than 7-day treatment.…”
Section: Fluoroquinolone Smentioning
confidence: 99%